Persepsi Mahasiswa terhadap Metode Dakwah Ustadz Abdul Somad, Lc., MA (Studi Kasus pada Mahasiswa Jurusan KPI Fakultas Dakwah dan Komunikasi UIN Raden Fatah Palembang angkatan 2015) - Irham Sugandhi; Manalullaili Manalullaili; M Amin Sihabuddin (Jurnal Komunikasi Islam dan Kehumasan (JKPI), 2018)
This thesis is entitled: “Persepsi Mahasiswa terhadap Metode Dakwah Ustadz Abdul Somad, Lc., MA (Studi Kasus pada Mahasiswa Jurusan KPI Fakultas Dakwah dan Komunikasi UIN Raden Fatah Palembang angkatan 2015) with the problems in this study are: What is da’wah method that often used by Ustadz Abdul Somad, Lc., MA and What is the perception of KPI Students in academic year 2015 of UIN Raden Fatah Palembang towards the method of da'wah Ustadz Abdul Somad, Lc., MA. Guided by Suharsimi Arikunto, if the population is less than 100 people it is better taken all, whereas if the population is larger then it can be taken 10-15% or 20-25%. In this study the population is all students majoring in KPI 2015, consist of 114 studentd. While the sample or respondents taken as many as 25% of 114 people, namely 28.5 rounded up to 30 respondents . The results of this study are: The method that is often used by Ustadz Abdul Somad, Lc., MA and good according to respondents is the question answer method and verbal method. While the method that is rarely used by Ustadz Abdul Somad, Lc., MA and is a discussion method.